Pelatihan Deteksi Dini dan Pencegahan Kanker Mulut pada Kader Lansia Posbindu Harapan Bekasi - Amtha, Rahmi; Hartanto, Firstine Kelsi; Sundjojo, Mikha; Ariyani, Annisaa i Putri; Yusra, Yohana; Dewi Kusuma, Riesta Paluvi; Tedja, Christian Henry; Herwanto, Tiffany; Winarto, Jessica Valerie; Natahnie, Fransiskus Arnold; Sudarmi, Elisabeth (Jurnal Abdimas Kesehatan (JAK), 2024)
Oral cancer is one of the malignancies whose numbers continue to increase every year throughout the world including Indonesia.  Oral cancer can be caused by multiple factors that are still unknown to many Indonesians. The WKRI Bekasi organization in collaboration with Pos Binaan Terpadu (PosBindu) Harapan Jaya has monitoring activities and early detection of risk factors for non-communicable diseases (including cancer) is a potential partner to become a cadre of education on how early detection, factors that trigger oral cancer and the role of oral hygiene in its prevention in the local community. The method chosen was counseling about oral cancer and training on how to carry out early detection in Posbindu elderly cadres. The aim is to increase the knowledge and ability of cadres to recognize abnormalities that have the potential to become oral cancer and be able to maintain oral health to prevent oral disease. The results of community service activities on cadres showed an increase in knowledge by 25 points (65%) and there was a significant difference between the level of knowledge of participants before and after training (p=0.000). In addition, cadres can demonstrate mouth-self-assessment very well and correctly under the direction of the educator team.  By training on oral cancer and how to perform oral self-examination on elderly cadres Posbindu Harapan Bekasi provides an opportunity for the community to be more aware of the development of oral cancer.